2010
DOI: 10.1371/journal.pone.0008796
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Linked Epidemics: The Case of Tuberculosis and HIV

Abstract: BackgroundThe tight epidemiological coupling between HIV and its associated opportunistic infections leads to challenges and opportunities for disease surveillance.Methodology/Principal FindingsWe review efforts of WHO and collaborating agencies to track and fight the TB/HIV co-epidemic, and discuss modeling—via mathematical, statistical, and computational approaches—as a means to identify disease indicators designed to integrate data from linked diseases in order to characterize how co-epidemics change in tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
(51 reference statements)
2
8
0
Order By: Relevance
“…These findings are corroborated in other studies by [31,53]. Looking beyond Kenya, studies by [54] revealed that TB appeared to outpace HIV in Rwanda and Burundi while HIV greatly outpaced TB in Mauritania, Senegal and The Gambia Joint temporal analysis is important when investigating the temporal coherency of epidemiological trends from the same area [54]. In our study, the shared temporal trend presented a steep decrease from 2012 to 2013 then an almost constant risk without any significant variation over time.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are corroborated in other studies by [31,53]. Looking beyond Kenya, studies by [54] revealed that TB appeared to outpace HIV in Rwanda and Burundi while HIV greatly outpaced TB in Mauritania, Senegal and The Gambia Joint temporal analysis is important when investigating the temporal coherency of epidemiological trends from the same area [54]. In our study, the shared temporal trend presented a steep decrease from 2012 to 2013 then an almost constant risk without any significant variation over time.…”
Section: Discussionsupporting
confidence: 89%
“…It is often described as a HIV, tuberculosis coepidemic. 19 However, testing for HIV infection in tuberculosis patients has not emerged as a routine practice in resource limited and developing countries like India. Only 22 (29.3%) out of 75 patients were tested for HIV and found negative.…”
Section: Discussionmentioning
confidence: 99%
“…Joint temporal analysis is important when investigating the temporal coherency of epidemiological trends from the same area [37]. In our study, the shared temporal trend an almost constant risk with minimal variation over time.…”
Section: Discussionmentioning
confidence: 80%